Thermal conductivity, viscosity, and heat transfer process in nanofluids: A critical review - Noorzadeh, Saeed; Sadegh Moghanlou, Farhad; Vajdi, Mohammad; Ataei, Mohammad (Journal of Composites and Compounds, 2020)
Heat transfer efficiency has always been at the center of attractions for many researchers and industries, and de-mand for higher efficiency methods and materials are increased in the last decades. Among the different methods of heat transfer enhancement, using nanofluids has proven to be an effective technique. In the present paper, the properties of nanofluids including viscosity, thermal conductivity as well as convective heat transfer are discussed and useful conclusions about the reported results by different researchers are presented. The effect of volume fraction, temperature, size and shape of particles, base fluid properties, and other factors on viscosity, and thermal conductivity of nanofluids are reviewed. Also, in the present manuscript, the methods of stable nanofluid prepara-tion, and the effective factors on the stability of nanofluids are exhibited in detail. Besides, a summarized number of experimental and mathematical studies on the properties, and stability of nanofluids are listed, compared, and analyzed. The works about the Nusselt number in fluids and nanofluids are presented in detail to determine the future challenges of nanofluids.